Welfare versus Work under a Negative Income Tax: Evidence from the Gary, Seattle, Denver and Manitoba Income Maintenance Experiments - Chris Riddell; W. Craig Riddell (Institute of Labor Economics (IZA), 2021)
The Income Maintenance Experiments have received renewed attention due to growing international interest in a Basic Income. Proponents viewed a Negative Income Tax as a replacement for traditional welfare with stronger work incentives and reduced poverty. However, existing labor supply estimates for single parents are uniformly negative. We re-assess the experimental evidence and find randomization failure in two NITs (Gary and Seattle). In Denver and Manitoba, we find a positive labor supply response for those on welfare prior to random assignment. Our results provide strong evidence that a NIT can increase work activity among single parents on welfare.
Keywords: C9; I38; J2; 330; negative income tax; welfare; income maintenance experiments; labour supply